Between Land and People: A Review of Socioeconomic Issues within the context of Rapid Development in Iskandar Malaysia (International Journal of Built Environment and Sustainability, 2016)
In response to globalization and economic competitiveness, Malaysia launched six economic development corridors, covering all the potential areas in Malaysia, and Johor Bahru is one of them. Iskandar Malaysia was launched in 2006 for future economic development in the country as well as to cater the needs of Johor Bahru to modernize its urban and economic infrastructure. Situated in a strategic location and space, Iskandar Malaysia is targeted to be the player of catalytic investment role that will bring direct and indirect investment to Johor. The whole landscape of Johor Bahru is now transforming dramatically, thus worrying the locals and the environmentalists. Environmental issues as well as the concern for social inequality issues have been raised by the locals. Hence, the aim of this study is to address the issues created by the rapid development of Iskandar Malaysia, particularly in Johor Bahru and Nusajaya. The objectives of this paper are to assess the consequences of the coastal land reclamation for Danga Bay waterfront city development and to identify the impact of new-build gentrification towards the local people. The research identifies key social and economic issues and the impacts of these issues have also been identified. To achieve the objective of the study a detailed review on secondary data has been done. The study found that more cooperation and attention from the local authorities, stakeholders and public is needed to ensure urban regeneration and to achieve the objective of social inclusiveness as promised by the vision of Iskandar Malaysia.